Protein phosphatase 1 is essential for Greatwall inactivation at mitotic exit - Heim, Andreas (EMBO Rep, 2015)
Entry into mitosis is mediated by the phosphorylation of key cell cycle regulators by cyclin-dependent kinase 1 (Cdk1). In Xenopus embryos, the M-phase-promoting activity of Cdk1 is antagonized by protein phosphatase PP2A-B55. Hence, to ensure robust cell cycle transitions, Cdk1 and PP2A-B55 must be regulated so that their activities are mutually exclusive. The mechanism underlying PP2A-B55 inactivation at mitotic entry is well understood: Cdk1-activated Greatwall (Gwl) kinase phosphorylates Ensa/Arpp19, thereby enabling them to bind to and inhibit PP2A-B55. However, the re-activation of PP2A-B55 during mitotic exit, which is essential for cell cycle progression, is less well understood. Here, we identify protein phosphatase PP1 as an essential component of the PP2A-B55 re-activation pathway in Xenopus embryo extracts. PP1 initiates the re-activation of PP2A-B55 by dephosphorylating Gwl. We provide evidence that PP1 targets the auto-phosphorylation site of Gwl, resulting in efficient Gwl inactivation. This step is necessary to facilitate subsequent complete dephosphorylation of Gwl by PP2A-B55. Thus, by identifying PP1 as the phosphatase initiating Gwl inactivation, our study provides the molecular explanation for how Cdk1 inactivation is coupled to PP2A-B55 re-activation at mitotic exit.